Quality of Participation and Quality of Science in Participatory Plant Breeding - International Center for Agricultural Research in the Dry Areas (International Center for Agricultural Research in the Dry Areas, 2003)
1) ICARDA's involvement in participatory plant breeding. 2) science in participatory plant breeding 3) quality of participation 4) institutionalization of participatory plant breeding 5) the future